Designing Systems of Drives of a Medical Robot Actuator - Kovalchuk, Alexander Kondratievich (International Journal of Natural Sciences Research, 2014)
The paper presents the results of a study that makes it possible to calculate power of drives in the degree of freedom of a medical robot with regard of dynamics of its actuator. Kinematic scheme of the robot is proposed, shown as a direct graph that contains no cycles. Values of the Denavit–Hartenberg parameters and reachability matrix have been obtained. The SolidWorks design system, elements of robot's design were developed, and values of masses, Torques of inertia, center of mass coordinates and other parameters of its main units required for simulation were obtained. Using an application specially developed in the MATLAB software package, a simulation was made, and numerical values of the matrix elements that are included into equation of the robot dynamics, as well as values of drives power in degrees of freedom were obtained.